Constitutional protection of the Human Right Dignity in UAE Law - Abdel Rahman, Rouaa; Bader, Ameera (Journal of Legal Sciences, 2023)
God Almighty created Man and made him his successor on Earth. He honored him above all other creatures and granted him all means to protect his human dignity, yet to date some societies violate and breach that protection. We are still hearing of the persecution of blacks in the USA and murdering Muslims in foreign countries even though these groups are entitled to the right to human dignity. The right to human dignity is a sacred right that is guaranteed for all individuals regardless of their color, sex, race, religion or origin. The real problem we are facing is that many societies do not provide sufficient protection for this right and do not put penalties and punishment in case this right is violated. There are numerous forms of the right to human dignity, including, but not limited to, the preservation of human dignity by prohibiting torture, assault, discrimination, violence, etc. Some countries protected that right directly by including it in their constitutions and legislations, while others set penalties only in case such right is violated without directly referring to it.In this research, we will shed light on the constitutional protection of the right to human dignity. First, we will explain the nature of the right to human dignity and the origin of it in the Abrahamic religions and international charters, then we will discuss some forms of this noble right, and finally we will show Position of the UAE legislation in this regard.